Potensi Ekonomi dalam Pengelolaan Persampahan Berkelanjutan Kota Surabaya - Muhammad Ramadhani Miftahul Asa; Belinda Ulfa Aulia (Dinasti Research, 2026)
Waste management remains a critical challenge for many nations. The continuous increase in waste generation not only diminishes public space and disrupts human activities but also degrades the overall quality of life. Conversely, effectively managed waste can yield significant benefits. One of the primary frameworks in sustainable waste management is the Circular Economy a model that integrates economic systems with long-term environmental sustainability. This study, titled